Observation of Gamma Irradiated Cotton Populations on Trend of Cotton Leafhopper Resistance Using Hopperburn Index - Hormchan, Praparat; Wongpiyasatid, Arunee; Piyapuntawanon, Somchai (Agriculture and Natural Resources, 2001)
The experiments were conducted during the 2000 and 2001 cotton growing seasons at Suwan Farm, Pakchong, Nakon Ratchasima to investigate the damage of gamma irradiated cotton populations caused by the cotton leafhopper Amrasca bigutulla bigutulla using hopperburn index. Preliminary observation on M1 populations of cotton varieties, SR2, R1, AP1 and AP2, was administered in the year 2000. After which the M2 seeds of SR2, R1, AP1 and AP2 from the first year were used in the second year test in RCB design with 4 replicates. The numbers of cotton jassid from 2 leaves, one from the top and the other from the middle portions of the canopy from 10 plants in 3 middle rows of each tested variety were recorded on Days 45, 60 and 75 after germination. Visual rating on leafhopper damage was employed and hopperburn index was calculated. It was found that on Day 45, M2 populations of every tested line expressed moderate resistance to the leafhopper except R1 susceptible as indicated by hopperburn indices. As the plants grew older to Days 60 and 75 the resistance reduced. The hopperburn indices were of negative correlation to the leafhopper whose amounts were high on Day 45 and decreased and rose again on Days 60 and 75, respectively. Scanning Electron Microscope (SEM) also showed AP2 and R1 with the greatest and lowest hair densities on Day 45 resulting in low and high hopperburn indices, respectively.